P88 Routine HIV testing in acute general medicine using a non-physician implemented model. (18th May 2015) - Buba, Amina; Fisher, Martin; Bentley, Colin; Roberts, Jonathan; Youssef, Elaney; Ibrahim, Mohammed Hassan; Brown, Michael; Richardson, Daniel
Abstract : Background/introduction: UK national guidelines recommend routine HIV testing in general medical admissions and primary care in areas where the HIV prevalence exceeds 2/1000 in the local population. The guidelines recommend further operational research to assess the feasibility and efficacy of different approaches to routine testing. A recent study showed that when a physician led model of testing is in place, 39.7% of all general medical patients are offered HIV tests. Aim(s)/objectives: Assess the feasibility and acceptability of a non-physician directed (NPD) model of HIV testing. Methods: Retrospective cohort study involving a review of the proportion of all medical admissions offered tests by a NPD model of HIV testing. Results: 57.9% (1973/3409) of all general medical admissions aged 18–79 were offered HIV tests. Acceptability was high with 96.7% (1908/1973) of offered patients having HIV tests. The mean age of patients offered and tested was 56.8 years. Discussion/conclusion: This study demonstrates superior feasibility and efficacy of a non-physician directed model of routine HIV testing. Although cost and culture remain important barriers of employing this strategy in many hospitals, the use of allied health professionals may be an important step in achieving National and International guidelines for HIV testing.